Assessment of some leucocytic enzymes in relation to etiopathogenesis of retention of fetal membranes in crossbred cows - Gupta, Sandeep Kumar; Kumar, Harendra; More, T (The Indian Journal of Animal Sciences, 2011)
The certain cationic peptides including myeloperoxidase (MPO), lysozyme, elastase and acid phosphatase (ACP) were analyzed in the cotyledons collected from cows with or without retention offetal membranes (RFM). A significantly lower (O.73±O.06 vs I.18±0.08,P<0.01) myeloperoxidase activity in the cotyledons of cows with RFM as compared to non-RFM cows indicated impairment ofneutrophil function at the fetomatemal union. Whereas, high activity of lysozyme (0.41±0. I2 vs 0.05±O.OO) and acid phosphatase (0. 12±O.O1 vs O.09±0.OO) in the cotyledons ofRFM cows reflect more severe trauma and/or inflammation at the fetomaternal union.